Perbandingan Metode Economic Order Quantity dan Period Order Quantity dalam Pengendalian Persediaan Bahan Baku pada Konveksi Hijab Arey Kecamatan Cicalengka - Rahmawati, Aulia Dwi; Herdian, Faldy (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to compare two methods of raw material inventory management, namely Economic Order Quantity (EOQ) and Periodic Order Quantity (POQ), in improving efficiency and reducing operational costs at Konveksi Arey Hijab. The main problem faced by this company is the irregularity in raw material inventory management, which causes wasteful costs, especially ordering costs and storage costs. Based on raw material purchase data in 2024, which recorded a total purchase of 26,203 kg with a total cost of IDR 1,834,573,300, this study uses a descriptive quantitative approach to compare the two methods. The results of the study show that the EOQ method produces lower inventory costs, namely IDR 16,568,074, compared to the POQ method. The application of the EOQ method can reduce the frequency of excessive ordering, while the POQ method is more effective for ordering periods that are adjusted to seasonal demand. This study recommends that Konveksi Arey Hijab adopt the EOQ method to optimize raw material inventory management, reduce wasteful costs, and improve the company's operational efficiency.